Prospective Assessment of the Prevalence of Enter Hyperoxalosis in Kidney Transplant Candidates. Issue 4 (29th March 2023) - Mejia, Christina; Tariq, Anam; Alotaibi, Manal; Lakhani, Laila; Greenspan, Wendy; Naqvi, Fizza; Alasfar, Sami; Brennan, Daniel C.
Abstract : Background: Enteric hyperoxalosis (EH) is an emerging cause of kidney transplantation (KT) dysfunction. We sought to determine the prevalence of EH and factors that affect plasma oxalate (POx) among at-risk KT candidates. Methods: We prospectively measured POx among KT candidates evaluated at our center from 2017 to 2020 with risk factors for EH namely bariatric surgery, inflammatory bowel disease, or cystic fibrosis. EH was defined by a POx ≥10 μmol/L. Period-prevalence of EH was calculated. We compared mean POx across 5 factors: underlying condition, chronic kidney disease (CKD) stage, dialysis modality, phosphate binder type, and body mass index. Results: Of 40 KT candidates screened, 23 had EH for a 4-y period prevalence of 58%. Mean POx was 21.6 ± 23.5 μmol/L ranging from 0 to 109.6 μmol/L. 40% of screened had POx >20 μmol/L. Sleeve gastrectomy was the most common underlying condition associated with EH. Mean POx did not differ by underlying condition ( P = 0.27), CKD stage ( P = 0.17), dialysis modality ( P = 0.68), phosphate binder ( P = 0.58), and body mass index ( P = 0.56). Conclusions: Bariatric surgery and inflammatory bowel disease were associated with a high prevalence of EH among KT candidates. Contrary to prior studies, sleeve gastrectomy was also associated with hyperoxalosis in advanced CKD. POx concentrations observed in EH reached levels associated with tissue and potentially allograft deposition. Concentrations can be as high as that seen in primary hyperoxaluria. More studies are needed to assess if POx is indeed a modifiable factor affecting allograft function in patients with EH.